A Preliminary Investigation to Decipher an Enigma Using Time-of-Flight Sensor - Uppal, Rohit (Universitas Airlangga, 2021)
Refractive index (RI) was characterized from the angle formed at the axis and slope of the linear fit of the measured perimeter of the loop of a waveguide vs. computed perimeter of the loop of the waveguide by using time-of-flight (TOF) sensor. The RI of uncladded commercially available waveguide was found to be 1.247 and 1.319 at 940 nm using ToF sensor and ellipsometer, respectively. The novel, simple and cost-effective technique may hold potential to initiate new avenues of research.